2022
DOI: 10.1177/00912174221107780
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among university students during distance learning period due to the COVID-19 pandemic: A cross sectional study at the University of Jordan

Abstract: Objective The COVID-19 pandemic led to a deviation from classical face-to-face learning to distance learning. Few studies examined burnout among university students during the distance learning period due to the COVID-19 pandemic. This study that aims to investigate the prevalence of burnout among university students during distance learning and the factors associated with it. Method A cross-sectional study was conducted among undergraduate students at the University of Jordan. The modified version of the Masl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Moreover, up to 97.4% and 90.8% of them were positive for emotional exhaustion and cynicism [ 23 ]. An online-based cross-sectional study among undergraduate students at Jordan showed that 6.6% of participants were found to have symptoms of burnout during distance learning period [ 40 ]. In line with previous findings, the present study indicated that the overall prevalence of high academic burnout among international university students during the new normal in Taiwan is as high as 12.01%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, up to 97.4% and 90.8% of them were positive for emotional exhaustion and cynicism [ 23 ]. An online-based cross-sectional study among undergraduate students at Jordan showed that 6.6% of participants were found to have symptoms of burnout during distance learning period [ 40 ]. In line with previous findings, the present study indicated that the overall prevalence of high academic burnout among international university students during the new normal in Taiwan is as high as 12.01%.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout is covered as it manifests in many different settings, such as the workplace [282][283][284][285], in groups including activists [6,130,131,[134][135][136]142] as well as students [286][287][288][289][290]. Burnout is also linked to the stress of having to constantly encounter systemic problems such as racism [7].…”
Section: Burnout and Disabled Peoplementioning
confidence: 99%
“…Research indicates that conflicting couples show the lowest levels of marital satisfaction and the highest likelihood of divorce Ying et al, 2023). When the intimate relationship ceases, numerous conflicts, repeated criticisms, silence, emotional disengagement, and unresolved problems arise, gradually leading to marital burnout (Chong et al, 2021;Toubasi et al, 2022;Younan et al, 2022). Marital burnout is an upsetting condition resulting from a mismatch between expectations and reality, and its extent depends on the couple's compatibility and beliefs.…”
Section: Introductionmentioning
confidence: 99%